PERANCANGAN ANIMASI MEDIA PEMBELAJARAN INTERAKTIF MATEMATIKA BERBASIS ANDROID - Jejen Jaeni; Agung Baitul Hikmah (Jurnal Teknik Informatika, 2015)
Abstract— World quintessence of education is currently experiencing a significant increase in line with improvements in the facilities and infrastructure to support learning and that it is also changing the current learning method of direct teaching methods in the classroom and through online media. But these methods still have disadvantages and advantages, for example is the limited time of learning and the internet connection itself, therefore it needs a learning media so that students can learn independently in understanding any instructional material taught anytime and anywhere. One is the mathematics which the authors restrict the development of interactive learning media of mathematics for the students of SMK/ SMA on the chapter geometry model of ADDIE, namely analysis, design, development, implementation and evaluation. Therefore, the author tries to make the media applications of mathematics which has android based application form that includes the chapter material geometries with video for explaining the example problems and exercises to test students' understanding by the multiple choice questions and essay receipts scoring system that will be stored in the form of high score table in order to evaluate the students' learning progress. Is by using this app students can learn independently in a fun way to choose the material that has not been understand or review materials that have been studied with the ease of access to learning media through smartphone devices.